Alkali lignin grafted chitosan adsorbent as well as preparation method and application thereof
By grafting alkali lignin, chitosan and isocyanate, an alkali lignin grafted chitosan adsorbent with synergistic adsorption effect was constructed, which solved the problems of low solubility and insufficient adsorption performance in an alkaline environment, and achieved the effect of efficient adsorption of organic dyes.
Patent Information
- Application Number
- CN202411940467.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
The problems of low solubility of chitosan in alkaline environments and prone to agglomeration in water limit their adsorption properties.
By reacting alkali lignin, chitosan and isocyanate at 100~110°C, an alkali lignin grafted chitosan adsorbent with a synergistic adsorption effect was constructed. The adsorbent significantly optimizes the adsorption process through the synergistic action of groups such as amino, hydroxyl, benzene ring and carbonyl, and improves the adsorption performance and dispersion.
The adsorption performance, rigidity and dispersion in water of adsorbent materials are significantly improved, and the adsorption of organic dyes is achieved efficiently, especially the adsorption amount of methylene blue dye is as high as 228 mg/g.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption materials, and in particular to an alkali lignin grafted chitosan adsorbent and a preparation method and application thereof. Background Art
[0002] With the rapid development of textile printing and dyeing, leather manufacturing and other industries, the dye industry has become an important part of the global chemical industry. However, the discharge of dye wastewater has brought serious pollution problems to the ecological environment. Therefore, it is urgent to develop efficient dye wastewater treatment technology.
[0003] As a recyclable renewable resource, chitosan has attracted much attention in recent years as environmental and resource problems have intensified. The amino (-NH2) and hydroxyl (-OH) groups on the chitosan molecular chain can electrostatically attract organic dyes and form hydrogen bonds to adsorb organic dyes. Although chitosan itself has a certain dye adsorption capacity, is low in price, and has high adsorption efficiency, it is an important member of biomass adsorption materials, but its low solubility in alkaline environments and easy aggregation in water limit its adsorption performance. Therefore, grafting modification of chitosan and introducing other functional groups to increase adsorption sites and optimize the adsorption window have become the key to improving its application potential.
[0004] In summary, the present invention develops a new adsorption material with high adsorption performance based on chitosan, which is not only of great significance for effectively solving pollution problems, but also a key step in realizing bio-matrix materials to promote national sustainable development. It is of great value in promoting the application of chitosan in more fields and promoting the development of green economy. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the present invention provides an alkali lignin grafted chitosan adsorbent with high adsorption performance and low cost, and a preparation method and application thereof.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] The invention provides an alkali lignin grafted chitosan adsorbent, which is obtained by reacting raw materials including alkali lignin, chitosan and isocyanate at 100-110°C.
[0008] In view of the problems of low solubility and insufficient adsorption performance of chitosan in an alkaline environment, the present invention grafts chitosan with a specific ratio of alkali lignin and isocyanate to construct a composite adsorbent with a synergistic adsorption effect, wherein the amino and hydroxyl groups in chitosan serve as key active sites for chemical adsorption, and can form hydrogen bonds or ionic bonds with polar functional groups (such as carboxyl groups, sulfonic acid groups, etc.) in the dye, thereby enhancing the interaction between the adsorbent material and the dye molecules, and effectively improving the adsorption performance and the density of adsorption sites; alkali lignin has a large number of hydroxyl groups, and both alkali lignin and isocyanate contain benzene rings, and the benzene rings can form non-covalent interactions with the aromatic rings in the dye molecules through the π-π stacking effect, thereby further increasing the adsorption capacity and selectivity of the adsorbent material. The present invention successfully grafts chitosan and lignin using isocyanate in the presence of a catalyst dibutyltin dilaurate to form a composite material with a rigid macromolecular network. The polarized structure of the carbonyl group in the composite material enables the adsorbent to combine more tightly with the organic dye, significantly improving the rigidity of the adsorbent material and its dispersibility in water. At the same time, the polarized carbonyl structure in the isocyanate molecule causes an open-chain reaction of chitosan through a nucleophilic reaction, thereby improving the openness of the molecular structure and exposing more amino groups and hydroxyl groups, further enhancing the adsorption capacity for organic dyes, and ensuring the uniformity of the dispersion of the adsorbent material in the aqueous phase, thereby providing basic support for efficient adsorption performance.
[0009] The present invention grafts alkali lignin onto chitosan through a simple grafting reaction to obtain an alkali lignin grafted chitosan adsorbent. The synergistic effect of amino, hydroxyl, benzene ring and carbonyl groups in the alkali lignin grafted chitosan adsorbent can significantly optimize the chemical and physical adsorption processes of the adsorbent, and has the characteristics of high-efficiency adsorption.
[0010] Furthermore, the mass ratio of the alkali lignin, chitosan and isocyanate is (5-17):(3-10):(29-41).
[0011] Furthermore, the mass ratio of the alkali lignin, chitosan and isocyanate is (8-11):(5-7):39.
[0012] Furthermore, the alkali lignin is alkaline lignin.
[0013] Furthermore, the isocyanate is 4,4-diphenylmethane diisocyanate.
[0014] Furthermore, the reaction time is 6 to 8 h.
[0015] Furthermore, the raw material also includes a catalyst, and the catalyst is dibutyltin dilaurate.
[0016] Furthermore, the amount of the catalyst used is 5% to 10% of the total mass of alkali lignin, chitosan and isocyanate.
[0017] The preparation method of the alkali lignin grafted chitosan adsorbent comprises the following steps:
[0018] S1. Alkali lignin and an organic solvent are uniformly mixed to obtain an alkali lignin slurry, which is recorded as slurry A; chitosan and an organic solvent are uniformly mixed to obtain a chitosan slurry, which is recorded as slurry B;
[0019] S2. Under the protection of inert gas, the slurry A and the slurry B are mixed evenly, and then isocyanate and a catalyst are added. After reacting at 100-110° C., the mixture is filtered, washed, dried, ground, and sieved to obtain an alkali lignin grafted chitosan adsorbent.
[0020] Furthermore, the organic solvent in step S1 is xylene.
[0021] Furthermore, the mixing method in step S1 is ultrasonic vibration.
[0022] Furthermore, the mass ratio of the alkali lignin to the organic solvent in the slurry A is 15:(35-52).
[0023] Furthermore, the mass ratio of chitosan to organic solvent in slurry B is 13:(35-52).
[0024] Furthermore, the inert gas in step S2 is nitrogen or argon.
[0025] Furthermore, the adsorption capacity of the alkali lignin grafted chitosan adsorbent for methylene blue dye is as high as 228 mg / g.
[0026] The invention also provides application of the alkali lignin grafted chitosan adsorbent in the treatment of organic dyes or polluted wastewater.
[0027] Compared with the prior art, the present invention is beneficial in that:
[0028] (1) The present invention grafts chitosan and alkali lignin by isocyanate to construct an alkali lignin grafted chitosan adsorbent with synergistic adsorption effect. The synergistic effect of amino, hydroxyl, benzene ring and carbonyl groups in the alkali lignin grafted chitosan adsorbent significantly enhances the chemical and physical adsorption process of the adsorbent, making it have the characteristics of high-efficiency adsorption.
[0029] (2) In the presence of isocyanate, the present invention successfully grafts chitosan and lignin to form a composite material with a rigid macromolecular network. The polarized structure of the carbonyl group enables the adsorbent and the organic dye molecules to be more tightly bound, significantly improving the rigidity and water dispersibility of the adsorbent material. The polarized carbonyl structure in the isocyanate opens the molecular structure of chitosan through a nucleophilic reaction, thereby increasing the openness of the molecular structure and exposing more amino groups, further enhancing the adsorption capacity for organic dyes. At the same time, it ensures the uniformity of the dispersion of the adsorbent material in the aqueous phase, providing a basic support for efficient adsorption performance.
[0030] (3) The alkali lignin grafted chitosan adsorbent provided by the present invention utilizes chitosan and lignin as renewable biomass raw materials, realizes the efficient removal of organic dyes in papermaking wastewater, reduces the production cost of the adsorbent, and provides a new way for the resource utilization of waste paper pulp. Through resource recycling and environmentally friendly design, the present invention provides a practical solution for sustainable development and ecological environmental protection, while promoting the efficient development and application of biomass materials, showing important economic and social value.
[0031] (4) The preparation method of the alkali lignin grafted chitosan adsorbent provided by the present invention is simple and easy to operate, does not involve expensive and dangerous chemicals, is green and environmentally friendly, and is conducive to large-scale production. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The invention provides an alkali lignin grafted chitosan adsorbent, which is obtained by reacting raw materials including alkali lignin, chitosan and 4,4-diphenylmethane diisocyanate at 100-110°C.
[0034] In some examples, the mass ratio of the alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate is (5-17): (3-10): (29-41).
[0035] In some examples, the reaction time is 6 to 8 h.
[0036] In some examples, the raw material further includes a catalyst, and the catalyst is dibutyltin dilaurate.
[0037] In some examples, the amount of the catalyst used is 5% to 10% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate.
[0038] The preparation method of the alkali lignin grafted chitosan adsorbent comprises the following steps:
[0039] S1. Alkali lignin and xylene are mixed evenly by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A; chitosan and xylene are mixed evenly by ultrasonic vibration to obtain a chitosan slurry, which is recorded as slurry B;
[0040] S2. Under the protection of inert gas, the slurry A and the slurry B are mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate are added. After reacting at 100-110° C., the mixture is filtered, washed, dried, ground, and sieved to obtain an alkali lignin grafted chitosan adsorbent.
[0041] In some examples, the mass ratio of the alkali lignin to the organic solvent in slurry A is 15:(35-52).
[0042] In some examples, the mass ratio of chitosan to organic solvent in slurry B is 13:(35-52).
[0043] In some examples, the inert gas in step S2 is nitrogen or argon.
[0044] In some examples, the adsorption capacity of the alkali lignin grafted chitosan adsorbent for methylene blue dye is as high as 228 mg / g.
[0045] In the following specific examples, unless otherwise specified, all the raw materials and reagents used were purchased conventionally.
[0046] Example 1
[0047] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0048] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0049] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0050] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added to make the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate 5:10:41, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain an alkali lignin grafted chitosan adsorbent.
[0051] Example 2
[0052] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0053] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0054] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0055] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added to make the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate 7:8:36, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate. Stir at a constant speed for 7 h at 105 ° C. Finally, filter and wash with deionized water for 3 times, dry at 80 ° C for 12 h, grind and pass through a 200-mesh sieve to obtain an alkali lignin grafted chitosan adsorbent.
[0056] Example 3
[0057] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0058] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0059] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0060] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added, so that the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate was 10:6:39, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105°C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80°C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin-grafted chitosan adsorbent.
[0061] Example 4
[0062] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0063] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0064] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0065] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added to make the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate 14:4:33, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate. Stir at a constant speed for 7 h at 105 ° C. Finally, filter and wash with deionized water for 3 times, dry at 80 ° C for 12 h, grind and pass through a 200-mesh sieve to obtain an alkali lignin grafted chitosan adsorbent.
[0066] Example 5
[0067] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0068] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0069] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0070] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added, so that the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate was 17:3:29, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105°C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80°C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin-grafted chitosan adsorbent.
[0071] Comparative Example 1
[0072] A chitosan adsorbent, the preparation steps are as follows:
[0073] S1. Add chitosan and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0074] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve them, which was recorded as slurry B;
[0075] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added to make the mass ratio of chitosan and 4,4-diphenylmethane diisocyanate 16:39, and the amount of dibutyltin dilaurate was 8% of the total mass of chitosan and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105°C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80°C for 12 h, ground and passed through a 200-mesh sieve to obtain a chitosan adsorbent.
[0076] Comparative Example 2
[0077] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0078] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0079] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0080] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then dibutyltin dilaurate was added to make the mass ratio of alkali lignin to chitosan 10:6, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin and chitosan, and stirred at a constant speed for 7 h at 105 °C. Finally, it was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin grafted chitosan adsorbent.
[0081] Comparative Example 3
[0082] An alkali lignin adsorbent, the preparation steps are as follows:
[0083] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0084] S2, adding alkali lignin and xylene in a mass ratio of 13:43 into a beaker, and dispersing and dissolving by ultrasonic vibration is recorded as slurry B;
[0085] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then 4,4-diphenylmethane diisocyanate and dibutyltin dilaurate were added, so that the mass ratio of alkali lignin and 4,4-diphenylmethane diisocyanate was 16:39, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105°C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80°C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin adsorbent.
[0086] Comparative Example 4
[0087] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0088] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0089] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0090] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and 4, 4-diphenylmethane diisocyanate and dibutyltin dilaurate were added at the same time, so that the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate was 3:13:39, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin-grafted chitosan adsorbent.
[0091] Comparative Example 5
[0092] An alkali lignin grafted chitosan adsorbent, the preparation steps are as follows:
[0093] S1. Add alkali lignin and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkali lignin slurry, which is recorded as slurry A;
[0094] S2, chitosan and xylene were added into a beaker at a mass ratio of 13:43, and ultrasonically vibrated to disperse and dissolve the chitosan to obtain a chitosan slurry, which was recorded as slurry B;
[0095] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and 4, 4-diphenylmethane diisocyanate and dibutyltin dilaurate were added at the same time, so that the mass ratio of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate was 15:1:39, and the amount of dibutyltin dilaurate was 8% of the total mass of alkali lignin, chitosan, and 4,4-diphenylmethane diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain an alkali lignin-grafted chitosan adsorbent.
[0096] Application Examples
[0097] Analytical-grade reagent methylene blue was added to deionized water to prepare 1 L of methylene blue solution with an initial concentration of 200 mg / L. Then 20 mg of adsorbent was weighed and added to the methylene blue solution. The mixture was stirred at a constant speed at 25 °C for 3 h. The concentration of methylene blue after adsorption was measured by atomic absorption spectrophotometry, and the adsorption amount was calculated. The test results are shown in Table 1.
[0098] The equilibrium adsorption amount mentioned in the test is the result of the adsorbent reaching equilibrium by oscillating adsorption of a certain concentration of organic dye solution. The concentration of organic dye before and after adsorption is determined by atomic absorption spectrophotometry, and the adsorption amount is calculated as follows:
[0099]
[0100] In the formula, is the equilibrium adsorption capacity, the unit is mg / g, C o is the initial concentration of the organic dye in the solution before adsorption, expressed in mg / L, C e is the equilibrium concentration of the organic dye in the remaining solution after adsorption, recorded in mg / L, m is the mass of the adsorbent, recorded in g, and V is the volume of the organic dye solution, recorded in L.
[0101] Table 1: Test results of adsorbing methylene blue by adsorbents prepared in Examples 1 to 5 and Comparative Examples 1 to 5
[0102]
[0103] It can be seen from Table 1 that the adsorbent prepared in Example 3 has the highest content of methylene blue adsorbed, and the adsorbent prepared in Comparative Example 1 has the lowest content of methylene blue adsorbed. Compared with Example 3, in Comparative Example 1, chitosan is used as a raw material, and chitosan reacts within or between molecules to obtain a chitosan adsorbent, and its adsorption amount is much lower than that of the alkali lignin grafted chitosan adsorbent prepared by the present invention. The reason may be that natural chitosan only has its own adsorption groups, and its adsorption effect on methylene blue is relatively limited; compared with Example 3, no 4,4-diphenylmethane diisocyanate is added in Comparative Example 2, and no grafting reaction occurs between chitosan and alkali lignin. They are only combined by electrostatic adsorption such as hydrogen bonds, and therefore cannot effectively improve the dispersion effect of the adsorbent, resulting in poor adsorption of the adsorbent in Comparative Example 2; compared with Example 3, in Comparative Example 3, alkali lignin is used as a raw material, and alkali lignin reacts within or between molecules to obtain an alkali lignin adsorbent, and its adsorption amount is much lower than that of the alkali lignin grafted chitosan adsorbent prepared by the present invention. Although the hydroxyl and benzene ring groups contained in the alkali lignin have a certain adsorption effect on methylene blue, the adsorption effect is limited. Compared with Example 3, in Comparative Example 4, lignin was reduced and the amount of chitosan was increased to a mass ratio of 3:13. The adsorption amount of the prepared adsorbent was worse than that of the adsorbent prepared in the present invention. The reason may be that the very small amount of alkali lignin resulted in a reduction in the adsorption sites provided by the alkali lignin, and a large amount of chitosan did not participate in the grafting reaction. Compared with Example 3, lignin was increased in Comparative Example 5 and the amount of chitosan was reduced. The reason for the reduction in adsorption was the same as that of Comparative Example 4, which was due to the reduction in active sites.
[0104] In summary, the present invention reacts a specific ratio of alkali lignin, isocyanate and chitosan at 100-110 ° C to obtain an alkali lignin grafted chitosan adsorbent. The method is simple to operate and low in cost. The prepared alkali lignin grafted chitosan adsorbent has excellent dye adsorption capacity, wherein the adsorbent has an adsorption capacity of up to 228 mg / g for methylene blue dye, and can be widely used in the treatment of organic dyes or polluted wastewater.
[0105] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. An alkali lignin grafted chitosan adsorbent, characterized in that: The alkali lignin grafted chitosan adsorbent is obtained by reacting raw materials including alkali lignin, chitosan and isocyanate at 100-110°C.
2. The alkali lignin grafted chitosan adsorbent according to claim 1, characterized in that: The mass ratio of the alkali lignin, chitosan and isocyanate is (5-17):(3-10):(29-41).
3. The alkali lignin grafted chitosan adsorbent according to claim 2, characterized in that: The mass ratio of the alkali lignin, chitosan and isocyanate is (8-11):(5-7):
39.
4. The alkali lignin grafted chitosan adsorbent according to claim 1, characterized in that: The isocyanate is 4,4-diphenylmethane diisocyanate.
5. The alkali lignin grafted chitosan adsorbent according to claim 1, characterized in that: The raw materials also include a catalyst, and the catalyst is dibutyltin dilaurate.
6. The alkali lignin grafted chitosan adsorbent according to claim 1, characterized in that: The reaction time is 6 to 8 h.
7. The method for preparing an alkali lignin grafted chitosan adsorbent according to any one of claims 1 to 6, characterized in that: The steps include: S1. Alkali lignin and an organic solvent are uniformly mixed to obtain an alkali lignin slurry, which is recorded as slurry A; chitosan and an organic solvent are uniformly mixed to obtain a chitosan slurry, which is recorded as slurry B; S2. Under the protection of inert gas, the slurry A and the slurry B are mixed evenly, and then isocyanate and a catalyst are added, and the mixture is reacted at 100-110° C. to obtain an alkali lignin grafted chitosan adsorbent.
8. The method for preparing an alkali lignin grafted chitosan adsorbent according to claim 6, characterized in that: The mass ratio of the alkali lignin to the organic solvent in the slurry A is 15:(35-52).
9. The method for preparing an alkali lignin grafted chitosan adsorbent according to claim 6, characterized in that: The mass ratio of chitosan to organic solvent in slurry B is 13:(35-52).
10. Use of the adsorbent prepared by the method according to any one of claims 7 to 9 in the treatment of organic dyes or polluted wastewater.